Demographic Characteristics and Personality Disorders in People With Gender Dysphoria in East Azerbaijan Province, Iran - Shafiei Kandjani, Ali Reza; Sadeghpour, Sona; Samadirad, Bahram; Mehrara, Arezoo; Hosseinnejad, Parisa; Shalchi, Behzad (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Gender identity is an important part of human identity. It is a personal conception of oneself as male or female. One of the major goals of treatment for individuals with Gender Dysphoria (GD) is to treat comorbid psychological and psychiatric disorders such as personality disorders. The present study aims to investigate demographic characteristics and personality disorders in people with GD seeking gender reassignment therapy in East Azerbaijan Province, Iran. Methods: In this descriptive cross-sectional study, study population consists of all patients with GD referred to the forensic medicine centers in East Azerbaijan province during 2016-2020, of whom 61 (21 males and 40 females) were selected using a convenience sampling method. Their age, gender, educational level, and marital status were recorded and their personality profile was assessed by the Millon Clinical Multiaxial Inventory–III. Results: The frequency (percentage) of Cluster A, B and C personality disorders in males were 0(0%), 9(50%) and 2(11.10%), while in females they were 1(5.56%), 4(22.40%), and 2(11.10%), respectively. The frequency (percentage) of antisocial, obsessive, borderline, avoidant, narcissistic, histrionic, and paranoid personality disorders in males were 4(22.2%), 2(11.10%), 3(16.67%), 0(0%), 0(0%), 2(11.10%), and 0(0%), while in females they were 4(22.20%), 1(5.56%), 3(16.67%), 1(5.56%), 1(5.56%), 2(11.10%), and 1(5.56%), respectively. The prevalence of different clusters (P=0.34) and types (P=0.18) of personality disorders was not significantly different between males and females. Conclusion: Personality disorders are comorbid with GD. They exist in one-third of patients with GD in East Azerbaijan Province. Personality disorders are significantly more prevalent in male patients with GD than in females.